Expression and Functional Characterization of Various Chaperon-Usher Fimbriae, Curli Fimbriae, and Type 4 Pili of Enterohemorrhagic Escherichia coli O157:H7 Sakai - Elpers, Laura; Hensel, Michael (Frontiers in Microbiology, 2020)
Enterohemorrhagic Escherichia coli (EHEC) is a highly pathogenic strain leading to hemorrhagic colitis and to the hemolytic-uremic syndrome (HUS) in humans. The mechanisms by which pathogenic E. coli infect and colonize humans leading to the typical disease pattern are in focus of many investigations. The adhesion of EHEC to epithelial cells by the coordinated translocation of receptor Tir and surface expression of corresponding adhesin intimin is a key event in host–pathogen-interaction. However, less is known about other adhesins encoded by EHEC, especially about the complex set of fimbrial adhesins varying among various serotypes. Here, we investigate EHEC serotype O157:H7 strain Sakai possessing at least 16 putative fimbrial gene clusters. Using a synthetic heterologous expression system in a non-pathogenic E. coli strain, a subset of 6 gene clusters for fimbrial adhesins was analyzed. We were able to visualize surface expression of two γ1 class fimbriae (Fim and Ycb), two γ4 class fimbriae (Yad and Yeh), and two fimbrial adhesins which are assembled by the nucleation/precipitation pathway (Curli fimbriae), and by a type 2 secretion system (type 4 pili). Further, we elucidated the impact of these fimbrial adhesins in adhesion to various epithelial cells lines (HeLa, MDCK, and CaCo2), and the contribution on biofilm formation. We demonstrate the ultrastructure of Fim fimbriae and Yad fimbriae of EHEC Sakai, and Yeh fimbriae of E. coli in general. The involvement of Fim fimbriae of EHEC Sakai to adhesion to various epithelial cell lines, and contribution to biofilm formation is reported here. Our approach provides first ultrastructural and functional data for novel EHEC adhesins, and enables further understanding of the involvement of fimbrial adhesins in pathogenesis of EHEC Sakai.